Urban forests management. Design-driven technological routes for wood waste valuing - Cyntia Santos Malaguti de Sousa; Tomás Queiroz Ferreira Barata; Caio Dutra Profirio de Souza; Felipe Gustavo de Melo (Agathón)
Urban forestry is fundamental to cities’ quality of life and resilience and deserves an effort in planning, management and expansion. This article aims to analyse and systematise technological routes to indicate potential uses of urban tree residues, focusing on the research, teaching and extension activities of the University of São Paulo, Brazil. The methodological procedures consist of: 1) review of related literature; 2) identification and classification of species; 3) analysis of tree management procedures; 4) implementation of experimental projective and productive processes and; 5) conducting capacity building and technology transfer workshops. The results present a mapping of the technological routes indicating a transition to a more sustainable production model for this urban natural capital.